GROUPING OF KABOLA, HAMAP, AND KLON LANGUAGES ON THE ISLAND OF ALOR, EAST NUSA TENGGARA - Adhiti, Ida Ayu Iran; Mbete, Aron Meko; Putra, A.A. Putu; Budasi, I Gede (e-Journal of Linguistics, 2016)
Associated with the language development in Nusa Tenggara Timur (East Nusa Tenggara), especially in Alor Regency, in-depth research needs to be done to the linguistic phenomenon. The phenomenon involves the grouping of languages genetically. Overall language data collection is analyzed by comparative linguistic study Regional languages in Alor regency show unique characteristics, as inspite of the people place to stay between one tribe to another tribe is quite close and there are differences in the language. The diversity of regional languages has an enormous influence on public life. Research on language groupings Kabola, Hamap, and Klon language Clones in Alor Island i is based on the study of the theory of comparative historical linguistics, supported by theory of Antila (1972) and Bynon theory (1979). The study is quantitative ??using syncomparative lexicostatistic technique with 200 vocabulary of Swadesh (1972). Based on lexicostatistic techniques, between Kabola language and the language of Hamap, the highest percentage was found, namely 53%. The percentage between Hamap and Klon languages reached 46%. Furthermore, the percentage between Kabola and Koln languages reached 36% which is the lowest cognate. The three languages ??percentage indicates a kinship of language, compared with fifteen other languages ??as neighbouring languages. The lowest cognate reached an average of 1.5% and the highest ceognat average is 11.1%. The fifteen languages ??can be categorized as mesofilium, microfilium, and a family of languages ??that belong to the languages ??that are not related.
Keywords: grouping and comparative historical linguistics